RELIABILITY OF ASSESSMENT METHODS OF GAME PERFORMANCE AND GAME SKILLS IN SCHOOL BASKETBALL (Fiep Bulletin - online, 2014)
The aim of the study was to design assessment methods of game performance and game skills for school basketball. The assessment method of game performance was constructed on the basis of reliable and valid measurement instruments in team sports, Game Performance Assessment Instrument and Team Sport Assessment Procedure, which enable teachers to evaluate the ability to solve tactical problems by making decisions, moving appropriately and executing skills. Three experts were engaged to verify the reliability of the method by observing and coding performance behaviours in basketball matches through digital recording. Kendall‘s coefficient was used to evaluate the data. Game abilities were measured by Under basket shot test, Dribbling and Push pass for accuracy test. Reliability was verified by test – retest method on a sample of 263 pupils in the age of 14 to 18 years. Methods of statistical analysis, intraclass correlationand standard test’s error were used to evaluate the data. Reliability of the assessment method of game performance was W=0.86 (p
Keywords: game performance; game skills; assessments methods; reliability; basketball